Vegetation C: N: P stoichiometry and ecosystem carbon storage under different grazing patterns on the Tibetan Plateau - He, Guoxing; Liu, Xiaoni; Li, Yali; Ji, Tong (Frontiers in Plant Science, 2025)
IntroductionGrazing is a significant driver of grassland ecosystems changes, but the relationship between plant functional groups’ carbon (C): nitrogen (N): phosphorus (P) stoichiometry ratios and ecosystem C storage under different grazing management patterns remains uncertain.MethodsThis study investigated alpine meadows on the northeastern edge of the Tibetan Plateau, comparing four grazing patterns: banned grazing (BG), growing season rest-grazing (RG), traditional rest-grazing (TG), and continuous grazing (CG). We assessed the effects of these grazing patterns on plant functional group nutrient, C: N: P stoichiometry, and ecosystem C storage. The results provided valuable insights to support sustainable management strategies in alpine meadow ecosystems.Results and discussionThe results indicated that BG and RG enhanced nutrient enrichment, vegetation, soil, and ecosystem C storage. BG, RG, and TG increased aboveground C: N ratios but decreased C: P and N: P ratios. Grazing patterns indirectly influence ecosystem C storage by regulating plant stoichiometry and biomass allocation among functional groups. AGB of grasses is significantly positively correlated with ecosystem C storage (R² = 0.96), serving as the key driver of changes in C storage. In conclusion, maintaining biomass balance among functional groups and the C: N: P stoichiometry of plants is vital for preserving ecosystem C storage under grazing disturbances. It is essential that future management strategies incorporate these aspects to effectively protect and enhance C sequestration in alpine meadows.